Teachers’ Beliefs About Multilingualism in Early Childhood Education Settings: A Scoping Review - Zhijun Zheng (Education Sciences, 2025)
There is an increasing number of multilingual children attending early childhood education and care (ECEC) settings around the world. Early childhood teachers play a crucial role in supporting these multilingual young children. As teachers’ teaching practices are directed by their beliefs, it is significant to understand early childhood teachers’ beliefs about multilingualism in the existing literature in order to better support multilingual children. From 14 studies, this review categorised three main themes of early childhood teachers’ beliefs about multilingualism: multilingualism as a problem, multilingualism as a right, and concerns about multilingualism as a resource. Two studies examined factors associated with the variation in teachers’ beliefs. The findings of this review summarised various perspectives of teachers’ misconceptions and negative beliefs about multilingualism, although a small number of studies reported teachers’ positive beliefs about multilingualism in ECEC. This review addresses early childhood teachers’ knowledge gaps in child language development and multilingual pedagogies. In addition, this review identifies several research gaps for future studies. For example, more studies conducted in non-Western contexts and studies on teachers’ beliefs about supporting multilingual infants and toddlers are much needed. This review also contributes to informing future directions for professional development to empower early childhood teachers to support multilingualism.